Analisis Efektivitas Pengiriman Barang pada PT Tiki Jalur Nugraha Ekakurir (JNE) dalam Meningkatkan Kepuasan Pelanggan - Bella Uci Sapitri Br S Meliala1; Ariqa Shafa Nurelf; April Novi Kristiani Telaumbanua; Irwan Nopian Sinaga (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the effectiveness of goods delivery at PT TIKI Jalur Nugraha Ekakurir (JNE) and its impact on customer satisfaction, focusing on the application of Total Quality Management (TQM) principles. The research method used is a quantitative survey with purposive sampling technique, where data is collected through questionnaires distributed to customers. The results show that the application of TQM, which includes employee involvement, continuous improvement, and customer focus, significantly enhances delivery effectiveness. Furthermore, regression analysis indicates that delivery effectiveness positively influences customer satisfaction. This study recommends that PT JNE continue to strengthen the application of TQM in its operations to improve service quality and customer satisfaction.